1996
DOI: 10.1002/pc.10593
|View full text |Cite
|
Sign up to set email alerts
|

Polymer encapsulation of glass filler in ternary PP/PA‐6/glass blends

Abstract: The morphology and rheology of ternary isotactic polypropylene (PP)/polyamide‐6 (PA‐6)/glass blends is investigated and contrasted with the behavior of two‐component (binary) PP/PA‐6 blends. Injection molded samples of binary blends exhibit an interlayer slip morphology for both PP and PA‐6 as the matrix and the blend shear viscosity is lower than expected from a rule of mixtures. The morphology of ternary blends is dependent on the choice of the matrix phase. In ternary blends with a PA‐6 matrix, the PP domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Earlier work showed that the most important factors that can determine phase morphology is surface treatment of the rigid particles. Most previous studies have focused on the relationship between phase morphology and mechanical properties in PP-rubber-filler systems [5][6][7][8][9][10]. To our knowledge, there is no known significance effort focusing on using three and four-point bending tests to investigate the fracture mechanism of PP-CaCO 3 -EPR hybrid composites.…”
Section: Introductionmentioning
confidence: 95%
“…Earlier work showed that the most important factors that can determine phase morphology is surface treatment of the rigid particles. Most previous studies have focused on the relationship between phase morphology and mechanical properties in PP-rubber-filler systems [5][6][7][8][9][10]. To our knowledge, there is no known significance effort focusing on using three and four-point bending tests to investigate the fracture mechanism of PP-CaCO 3 -EPR hybrid composites.…”
Section: Introductionmentioning
confidence: 95%
“…The mechanical properties of ternary polymer composites depend upon their composition and structure (8)(9)(10)(11)(12)(13)(14). Two extreme morphologies can be considered: the filler particles and the minor component are dispersed separately in the matrix, or the minor component encapsulates the filler particles.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the crystallization temperature of the PA‐6 in the presence of MWCNT corresponds to the heterogeneous nucleation effect of the nanotubes . According to Benderly et al, the nanofiller acts as a nucleating agent for nylon‐6 provided that it is located within this phase in the blends. Thus, it is an indication of presence of nanotubes in the PA‐6 matrix.…”
Section: Resultsmentioning
confidence: 99%